Ekosufisme Syekh Nawawi Al-Bantani sebagai Paradigma Etika Lingkungan Islam: Analisis Ontologis, Epistemologis, dan Etis - Uup Gufron; Kartono Kartono (Jurnal Teologi Islam, 2026)
The global environmental crisis has encouraged the development of environmental ethics rooted in religious and spiritual values. This study aims to reconstruct Syekh Nawawi Al-Bantani's eco-Sufism as a paradigm of Islamic environmental ethics through ontological, epistemological, and ethical analyses. The research employed a qualitative library research approach using the major works of Syekh Nawawi Al-Bantani as primary sources and relevant scholarly literature on eco-Sufism, Islamic eco-theology, and environmental ethics as secondary sources. Data were collected through documentation and analyzed using content analysis integrated with the philosophy of Islamic thought. The findings reveal that, ontologically, nature is regarded as God's creation and a manifestation of divine signs that must be preserved. Epistemologically, environmental awareness is constructed through the integration of the Qur'an, Hadith, reason, and spiritual experience. Ethically, the principles of khilāfah, amānah, mīzān, zuhd, qanā'ah, and iḥsān constitute the moral foundation for environmental stewardship. The novelty of this study lies in reconstructing Syekh Nawawi Al-Bantani's eco-Sufism into an integrated conceptual framework that contributes to the development of contemporary Islamic environmental ethics and enriches theological discourse on ecological sustainability.